E-Service Quality Analysis of the MyTelkomsel Application Using CSI, IPA, and PGCV - Ananda Khoirunnisa; Dwi Rosa Indah; Ardina Ariani; Ari Wedhasmara; Naretha Kawadha Pasemah Gumay; M. Rudi Sanjaya; Mukhlis Febriady (Universitas Multimedia Nusantara, 2026)
This study evaluates the e-service quality of the MyTelkomsel application in response to ongoing user concerns, particularly slow service response and the limited effectiveness of the automated support system. A structured questionnaire based on the five SERVQUAL dimensions was used and demonstrated strong validity and reliability. Data were collected from one hundred users in Java and Sumatera. The analysis combined three methods: the Customer Satisfaction Index, Importance Performance Analysis, and Potential Gain in Customer Value. The findings show that the application achieved a Customer Satisfaction Index score of 67.75 percent, indicating that users are generally satisfied but expect further improvement. The Importance Performance Analysis recorded a suitability level of 74.54 percent, with several attributes placed in the high-importance low-performance quadrant, including login security, chatbot speed, complaint handling, and personal data protection. The Potential Gain in Customer Value results indicate that chatbot-related attributes and transaction reliability provide the highest potential for increasing customer value. Overall, the study highlights specific service attributes that require priority enhancement to strengthen user satisfaction and service quality.